Indigenous Australians and Liquor Licensing Legislation - Bourbon, D.; Saggers, S.; Gray, Dennis (1999)
This research project was designed to review liquor licensing and related legislation throughout Australia, and to develop recommendations aimed at ensuring that such legislation: furthers the objective of minimising the harm caused by alcohol among Indigenous Australians; promotes Indigenous community involvement in decision making regarding the availability of alcohol; and, is culturally appropriate.The study utilised a qualitative research methodology, which included review and analysis of existing legislation, a literature review, and analysis of written comment and interview data pertaining to liquor licensing legislation.